PEMANFAATAN PEKARANGAN UNTUK KETAHANAN PANGAN DI KELURAHAN LEMBAH SARI KECAMATAN RUMBAI KOTA PEKANBARU - Siswati, Latifa; Nizar, Rini; Ariyanto, Anto (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This community service project aims to enhance household food security by utilizing home yards in Lembah Sari Sub-district, Rumbai District, Pekanbaru City. The primary target group was housewives, who were trained to cultivate vegetable crops effectively and simply in their home gardens. The methods applied included counseling, technical training, distribution of agricultural inputs, and ongoing mentoring. The results showed a significant increase in participants' knowledge and skills in yard cultivation, along with a more optimal use of available yard space. The program contributed not only to improving household food security but also to providing opportunities for increasing family income and better access to healthy food. This activity proves that community-based home garden farming can be an effective strategy to strengthen local food security. Keywords: Food Security, Home Yard, Vegetable Cultivation, Women Empowerment, Community Service